Dichrostachys cinerea: Ethnomedicinal Uses, Phytochemistry and Pharmacological Activities - A Review - Mazimba, Ofentse; Kwape, Tebogo E.; Gaobotse, Goabaone (Natural Products Journal, The, 2022)
Indigenous and medicinal plants have proven crucial to the health of mankind for a very long time. Dichrostachys cinerea is a traditional herb used in the treatment of a variety of human diseases in African and Indian traditional medicine. This paper reviews the ethnomedicinal uses, phytochemical constituents, pharmacology, and toxicity of D. cinerea, in order to provide scientific consensus for further research and exploitation of the therapeutic potential of this plant. Information was accessed by literature searches in different sources including Science Direct, PubMed, and Google Scholar. The findings of this review paper highlight D. Cinerea as an important component of African and Indian traditional medicine. D. cinerea is traditionally used in the treatment of rheumatism, diabetes, coughs, asthma, kidney disorders, gonorrhea, syphilis, malaria, tuberculosis, epilepsy, snake bites, pains, wounds, boils, burns, toothache, headache, and scabies. D. cinerea displays diverse phytochemistry, with a wide range of isolated compounds that have well-documented biological activities. D. cinerea has demonstrated both in vitro and in vivo biological activities. In vitro, biological activities exhibited include enzyme inhibition, antibacterial, anti-fungal, and antimalarial activities. In vivo activities demonstrated by D. cinerea include anti-inflammatory, antidiarrheal, anti-analgesic, hepatoprotective, anti-urolithiatic, anti-lice, anti-dandruff, and neuropharmacological activities. Animal studies have elucidated the non-toxicity of D. cinerea for the ethanol root extract and methanol and water leaf extracts. It is vital that future studies on D. cinerea focus on the mechanisms of action behind these biological activities for both the crude extract and its chemical compounds. These studies could lead to clinical trials to confirm biological activities found in animal studies. Further studies on multi-target network pharmacology, and molecular docking technology of D. cinerea sub fractions for enzyme inhibitions and neuropharmacological activities are of great importance and could accelerate the process of pharmaceutical development of this plant.
Keywords: biological activities